Câncer da Bexiga, seu Tratamento Cirúrgico - Vianna, João B. (1950)
Sixteen cases of bladder câncer werer seen by the author since 1938. Intermitent hematuria was the principal symptom. Four patients were females and twelve were males. Up to 1948 treatment was mostly conservative, partial cystectomy beeing the major operation. One of the patients submited to partial cistectomy had a fairly large tumor of the right lateral wall of the bladder (transitional cell carcinoma) and is free of symptoms for 3 years. After 1948 more radical operations were performed, 5 total cystectomies with pelvic gland disection beeing done. One patients is living and free from recurences for 21 months, although she has a bilateral hydronephrosis. One patients died two months after the operation from generalised metastases. One patient died 13 days after operation from lung atelectasis. One died 4 months after cystectomy, from renal insuficiency and another patient operated recently (3 months) is still free from recurence. The author has performed cystectomy and pelvic gland disection both extraperitonealy. The operation is probably more tedious to doo then the intraperitoneal one but is safer as regard to peritonal infection.